Synthesis of polyurethane/clay nanocomposites based palm oil polyol coating - Teuku Rihayat; Suryani Salim; Harry Agusnar; Fajri; Zaimahwati (Journal of Mechanical Engineering and Sciences, 2015)
In this study, we investigated the Polyurethane paint based on palm oil with the addition of nanoparticles montmorillonite as a heat-resistant. The composites with 1 wt%, 3 wt% and 5 wt% of bentonite filler content obtained by synthesizing in situ were investigated and compared to the neat polyurethane matrix material. The processing of bentonite for montmorillonite was done through several stages including: sedimentation, ultrasonication, dried, sieved with a 200 mesh sieve, then characterized. Untreated MMT were isolated and modified with CTAB. The addition of MMT into polyurethane, as much as 5% wt, can increase the heat as evidenced by the TGA test. The TGA results indicated an enhanced thermal stability, as compared to the neat polyurethane. The onset degradation of neat polyurethane and weight reduction began at a temperature of 50-150°C and completely decomposed at the temperatures of 380°C and for PU MKS-MMT reduction, the initial weight started at a temperature of 150-200°C in 5 %wt and decomposed in the end at a temperature of 490°C. In this research, we also tested the gloss adhesive polyurethane with the addition of MMT; the result stated that the addition of 5%wt MMT can improve the adhesion of polyurethane. The addition of MMT in polyurethane can also enhance the gloss polyurethane compared with polyurethane coated without the addition of MMT.